Multi-Walled Carbon Nanotubes (MWCNTs) Activate Apoptotic Pathway Through ER Stress: Does Surface Chemistry Matter? - Sun Y (Dove Medical Press, 2019)
Yongbing Sun,1 Jianping Gong,1 Yi Cao2 1National Engineering Research Center for Solid Preparation Technology of Chinese Medicines, Jiangxi University of Traditional Chinese Medicines, Jiangxi, Nanchang 330006, People’s Republic of China; 2Key Laboratory of Environment-Friendly Chemistry and Application of Ministry of Education, Laboratory of Biochemistry, College of Chemistry, Xiangtan University, Xiangtan 411105, People’s Republic of ChinaCorrespondence: Jianping GongNational Engineering Research Center for Solid Preparation Technology of Chinese Medicines, Jiangxi University of Traditional Chinese Medicines, Jiangxi, Nanchang 330006, People’s Republic of ChinaTel +86-0791-87119623Email gongjianping64@163.comPurpose: Physicochemical properties play a crucial role in determining the toxicity of multi-walled carbon nanotubes (MWCNTs). Recently we found that MWCNTs with longer length and smaller diameters could induce toxicity to human umbilical vein endothelial cells (HUVECs) through the activation of endoplasmic reticulum (ER) stress. In this study, we further investigated the possible contribution of hydroxylation and carboxylation to the cytotoxicity of MWCNTs.Methods: The HUVECs were exposed to pristine (code XFM19), hydroxylated (code XFM20; content of hydroxyl groups 1.76 wt%) and carboxylated (code XFM21; content of carboxyl groups 1.23 wt%) MWCNTs, respectively. Then, the internalization, cytotoxicity, oxidative stress and activation of apoptosis-ER stress pathway were measured.Results: In consequence, all types of MWCNTs could be internalized into the HUVECs, and the cellular viability was significantly reduced to a similar level. Moreover, the MWCNTs increased intracellular reactive oxygen species (ROS) and decreased glutathione (GSH) to similar levels, indicating their capacity of inducing oxidative stress. The Western blot results showed that all types of MWCNTs reduced BCL-2 and increased caspase-3, caspase-8, cleaved caspase-3 and cleaved caspase-8. The expression of ER stress gene DNA damage-inducible transcript 3 (DDIT3) and protein level of chop were only significantly induced by XFM20 and XFM21, whereas protein level of p-chop was promoted by XFM19 and XFM21. In addition, the pro-survival gene XBP-1s was significantly down-regulated by all types of MWCNTs.Conclusion: These results suggested that MWCNTs could induce cytotoxicity to HUVECs via the induction of oxidative stress and apoptosis-ER stress, whereas a low degree of hydroxylation or carboxylation did not affect the toxicity of MWCNTs to HUVECs.Keywords: multi-walled carbon nanotubes, MWCNTs, human umbilical vein endothelial cells, HUVECs, endoplasmic reticulum (ER) stress, hydroxylation, carboxylation, ER stress